Characteristics Of Presbicusis: A Literature Review - Nawirah Labambe; Andi Tenri Sanna; Destya Maulani; Andi Baso Sulaiman; Indah Hamriani (Sean Institute, 2024)
Hearing loss or deafness is the partial or complete inability to hear sounds in one or both ears. Hearing loss can occur at any age. The most common cause of hearing loss in the elderly is presbycusis.1 Presbycusis or known as age related hearing loss (ARHL) is a loss of hearing ability that occurs slowly with age. The method used is literature review with Narrative Review design. The results obtained in this literature are that there are 10 articles obtained with restrictions from 2020 - 2024 and in-depth analysis of the strengths and limitations of each article on the characteristics of presbyacusis has been carried out. 10 articles that discuss the characteristics of presbyacusis, 8 articles mention the characteristics of presbyacusis based on age, 8 articles mention the characteristics of presbyacusis based on gender. Based on the results of the identification and review of several in this literature review, it can be concluded that there are several characteristics of presbyacusis including age, gender and history of chronic disease. Early recognition of the diagnosis of presbyacusis is very important, because if left untreated it can have serious consequences on mental health, cognitive, and even physical health.